2019
DOI: 10.3390/ijerph16173197
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Cigarette and E-Cigarette Smoking among School Personnel in Shanghai, China: Prevalence and Determinants

Abstract: Smoking cigarettes and e-cigarettes is widely popular among Chinese students. Considering that school personnel are considered role models in the student community, we investigated the prevalence and determinants of such behavior among high school personnel in China so as to provide references for future related intervention measures. We used a stratified cluster sampling design on a total number of 3311 school employees recruited from 33 representative schools. Complex sampling analysis and logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
(54 reference statements)
3
4
1
Order By: Relevance
“…Our ndings were consistent with some prior prevalence studies in that males were more likely to smoke than females(males: females = 37.2:7.5) 9,[22][23][24] . However, gender disparities in e-cigarettes were lower than in smokes, which is also consistent with previous research studies [25][26][27] .…”
Section: Discussionsupporting
confidence: 92%
“…Our ndings were consistent with some prior prevalence studies in that males were more likely to smoke than females(males: females = 37.2:7.5) 9,[22][23][24] . However, gender disparities in e-cigarettes were lower than in smokes, which is also consistent with previous research studies [25][26][27] .…”
Section: Discussionsupporting
confidence: 92%
“…Other reasons include physiological changes during pregnancy. The Lange study published in 2018 found that the global prevalence of smoking during pregnancy is 1.7 %, which is lower than the prevalence found in this study (25). According to a study conducted by Kondracki in the United States, 9.5 % of pregnant women smoked, with 7 % smoking during pregnancy (26).…”
Section: Resultscontrasting
confidence: 49%
“…The common adverse events were mouth or throat irritation, anxiety, depressed mood, nausea, and insomnia [28, 29]. Smoking cigarettes and e‐cigarettes are widely popular among Chinese students, and 7.4% of cigarette users and 3.6% of e‐cigarette consumers were observed among 3194 participants [30]. E‐cigarette is increasingly popular among adults of 19‐29 years old in China [31], and the awareness and use of e‐cigarettes in China are lower than that in the US [32].…”
Section: Discussionmentioning
confidence: 99%